O futuro sustentável da matriz energética brasileira: a importância e viabilidade do etanol de segunda geração no período de transição com ênfase no setor de transportes. - Freitas, Ynaê Rossetti de (Universidade Federal de São Carlos, 2022)
Currently, about 80% of the primary energy produced in the world comes from non-renewable sources, mainly oil. As it is a fossil and limited reserve, dependence on oil imports causes numerous exchange and energy crises in countries that do not have this resource, such as Brazil. Despite being classified as an emerging country, about 47% of Brazil’s energy matrix is filled by renewable sources, a fact that is completely related to the country's historical competitiveness in ethanol and sugarcane. Despite the development of several alternatives to the use of petroleum derivatives in the transport sector, the consumption of fossil fuels is expected to grow by about 20% in the next 20 years, increasing carbon dioxide (CO2) emissions and their environmental consequences. The main initiatives with the potential to reduce the impact linked to this scenario are encouraging the use of biofuels and switching to new transport technologies (electric and hybrid vehicles). Even though it is constantly evolving, the adoption of electric vehicles in the short-medium term is not a reality, especially in countries with a low railway network, such as Brazil, a fact that makes biofuels even more attractive. In this context, it is known that Brazilian ethanol is produced from sugarcane, using both sucrose and sugarcane bagasse as energy sources. The use of bagasse has the advantage of increasing production without increasing the planted area, so the development of technologies for the production of bioethanol from lignocellulosic materials becomes promising for the production of second-generation ethanol in the transition period between consumption of petroleum derivatives and vehicular electrification, since sugarcane bagasse has enormous energy potential in tropical countries, due to the availability of land, privileged geographical position and favorable climate. The present work proposes to carry out a literature review based on the history of the sector, on the main motivations for the production of second-generation ethanol and conduct a technical and economic analysis of the construction of a production plant. As main outcomes, we can mention the positive panorama of the Brazilian energy matrix, both in financial and ecosystem aspects. In addition, promising results were observed for the generation of biofuel on an industrial scale.
The sustainable future of the brazilian energy matrix: the importance of the second generation ethanol in the transition period with emphasis on the transport sector.
Keywords: Energia; Bioetanol; Setor de transportes; Material lignocelulósico; Energy; Bioethanol; Sugarcane bagasse; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA